AN OVERVIEW OF THE DIRECT SELLING INDUSTRY - Alina-Maria Neațu (Annals of the University of Oradea: Economic Science, 2016)
Trade is at the heart of any economic system and, as such, the method through which it is accomplished is of paramount importance. Easily one of the oldest, if not the oldest, method to accomplish this is through the means of direct selling. However, even if it hides behind and apparent simplicity, direct sales remains one of the most important methods of distribution used by companies even to this day. In this paper we attempt to provide an overview of this industry, as it stands at the moment. We accomplish this objective by first presenting the concept, as it has evolved in the past and the shape it has taken in the present. This is followed up by an overview of the industry, at the global level, which is achieved by focusing on the current level of sales achieved annually, the number of employees currently working in this industry and the year on year growth which has been achieved during the past years. A slightly more detailed approach was used when describing the direct selling industry in Germany, due to the fact that it is one of the largest and fastest developing markets in the whole of Europe. The data that we use for this study has been obtained from the annual report published by the World Federation of Direct Selling Associations.